Zum Telos des Philänenexkurses in Sall. Iug. 79 - Rackow, Martin (Hyperboreus, 2022)
The tale of the Philaeni brothers in Sall. Iug. 79 not only brings the description of the war to a halt, it also pleases the reader. Moreover, it is used by the author as a reflection point, when it comes to Marius appealing to his audience only six chapters after the digression. Marius’ concept of virtus as well as that of Sallust himself as shown in the prooemium is illustrated by the heroic feat of the two Carthaginians who give their life for their people.